Cultural Exclusion and Critique In the Era of Good Intentions: Using Participatory Research to Transform Parent Roles in Urban School Reform - Dyrness, Andrea (Social justice, 2009)
The article presents research on parent participation in school reform in urban areas with a large immigrant population using participatory research methods. Focusing on how the critique of schools from marginalized parents can be censored or ignored, the research looks at the efforts of a Latino immigrant parents group Madres Unidas (Mothers United) in Oakland, California that was able to voice their criticisms of the schooling structure and collaborate with school officials to achieve positive change. The author places the research in the context of the "new civil rights era" in the 2000s in the U.S. defining the era as a time where racial inequality is fragmented across several system levels but not specifically stated by law.